2023
DOI: 10.1002/ijfe.2782
|View full text |Cite
|
Sign up to set email alerts
|

Mobile and internet usage, institutions and the trade balance: Evidence from African countries

Abstract: This study examines the influences of institutions, the Internet and mobile usage on the trade balance of African countries between 2003 and 2017. Our empirical results have been estimated with a panel‐corrected standard error method (PSCE) and they have been confirmed by several alternative techniques. First, the increase of internet usage and mobile usage has a significant negative effect on total and inter‐continental trade balances while these factors improve the intra‐African trade balances. Second, bette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 57 publications
1
7
0
Order By: Relevance
“…On the other hand, Nguyen et al (2018) scrutinized the relationship between IQU and CE for 36 developing economies by using the GMM approach during 2002–2015. From empirical evidence, they suggested that better IQU increases economic activities which lead to increased environmental pollution.…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, Nguyen et al (2018) scrutinized the relationship between IQU and CE for 36 developing economies by using the GMM approach during 2002–2015. From empirical evidence, they suggested that better IQU increases economic activities which lead to increased environmental pollution.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results indicated that a country's industrial sector must undergo a clean structural transformation to achieve environmental sustainability. Nguyen et al [26] assessed the relationship between economic integration, trade openness, and FDI inflows in relation to carbon emissions in developing nations by analyzing the period between 2002 and 2015. The results indicate a positive correlation between economic integration and carbon emissions, verifying the PH hypothesis.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, institutional frameworks are the rules of the game of humanity, which would impose constraints on economic agents. A strong institutional system such as greater government efficiency, higher control of corruption, and clearer regulatory quality can improve the efficiency of public expenditure and thus strengthen the effects of fiscal policies in the fight against energy poverty (Nguyen et al 2018 ). These facts lend importance to the study of how the quality of political institutions, more specifically how improving good governance eradicated energy poverty.…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%